Hand Radiographs in Skeletal Dysplasia: A Pictorial Review - S., Dheeksha D.; Chandola, Stuti; Jain, Aayush; Gupta, Neerja; Kabra, Madhulika; Jana, Manisha (Indian Journal of Radiology and Imaging, 2023)
Skeletal dysplasias or osteochondrodysplasias comprise a large heterogeneous group of genetic disorders and possess significant overlap on imaging, which adds to the dilemma of the reporting radiologist. These entities are routinely evaluated with a detailed skeletal survey and hand radiographs form a crucial part of a complete survey. Certain conditions have characteristic imaging findings that enable a diagnosis be made on hand radiograph alone. Additionally, hand radiographs may also demonstrate findings that may be suggestive of a particular diagnosis/differential diagnoses and would warrant further assessment for proving the same. We aim to demonstrate the use of hand radiographs in diagnosis of various such entities through this review. Although they cannot replace a complete skeletal survey in the diagnosis, hand radiographs performed for other indications might alert a radiologist to the diagnosis of an unsuspected skeletal dysplasia.
Keywords: skeletal dysplasia; hand radiographs; progressive pseudorheumatoid arthropathy; mucopolysaccharidosis